Life Cycle Greenhouse Gases (GHG) Analysis of Oil Palm Empty Fruit Bunch-Based Dimethyl Ether: A case study in Indonesia - Heryadi, Rudy (Proceedings of the International Conference on Green Technology; Vol 15 No 1 (2025): Proceeding of 15th International Conference on Green TechnologyDO - 10.18860/icgt.v15i1.3836, 2026)
The abundant residue of palm oil processing in Indonesia, such as oil palm empty fruit bunch (OPEFB), has the potential to be converted into dimethyl ether (DME) that can be used as an LPG substitute. Therefore, this study assesses the reduction of greenhouse gas (GHG) emissions when DME is utilised as a substitute for LPG in Indonesia. The reduction in GHG emissions was calculated using a life cycle analysis of GHG emissions for OPEFB-based DME, and the results were compared with those of LPG and coal-based DME. The results show that the life cycle GHG emission of OPEFB-based DME is 1.47 kg-CO2 eq kg-DME-1. The GHG emission that can be reduced when LPG is substituted with OPEFB-based DME is 30%. Compared with coalbased DME projected to substitute LPG in Indonesia, the GHG emission reduction is 73%. The environmental burden of OPEFBbased DME is lower than that of LPG and coal-based DME, which shows that OPEFB-based DME is a more sustainable alternative. This study demonstrates that OPEFB-based DME produced in Kalimantan, Indonesia, has excellent development potential, particularly when it meets the GHG emissions reduction criteria.